(untitled) - Hooks, William H.; Meisel, Paul (Milwaukee, Wis., 1997)
A boy has mixed feelings about his five-year-old brother Eli, who sticks close to him whether he is inventing a new soft drink or trick-or-treating on Halloween.
K-3
Keywords: Brothers; Fiction